Економічні інновації: рушійна сила технологічних змін. Концепція підривних інновацій - Варшава, О. (Baltic International Academy, 2018)
At present, the development of the Ukrainian economy in the conditions of rapid globalization processes and European integration is relevant. In order to ensure the competitiveness of the economy, it is essential to implement the necessary institutional changes and innovations. The concept of innovations, disruptive innovation and the importance of their implementation in economic processes in Ukraine is described in the paper. // Зараз актуальним є розвиток економіки України в умовах швидких глобалізаційних процесів і євроінтеграції. Для забезпечення конкурентоспроможності економіки потрібно втілювати необхідні інституційні зміни і впроваджувати інновації. У ра-боті викладені поняття інновацій, підривних інновацій і важливість їх впровадження в економічних процесах в Україні. Ключові слова: державна політика, економічний розвиток, економічне стимулювання. інновації, підривні інновації.
Keywords: руйнівні інновації; економічний розвиток; економічне стимулювання; інновації; державна політика; disruptive innovation; economic development; economic stimulation; innovation; state policy